The Role of Motivation in Improving Work Discipline in PT IP Employees - Khoirunnisaa, Alfina; Sungkono, Sungkono (Integrasi Sains Media, 2023)
This research uses qualitative methods to understand the object studied in depth. This research is used to determine how work motivation improves work discipline in PT IP employees. To get the human resources to contribute positively to all company activities in achieving its goals, every employee must be motivated to improve work discipline. Motivation is an essential thing to be considered by management if they want every employee to contribute positively to achieving company goals because, with motivation, an employee can have high enthusiasm in carrying out their duties.